Training Behavioral Reheasal untuk Mengurangi Kecemasan Sosial (Studi Pada Mahasiswa Berkepribadian Introvert) - Desi Erawati; Fathoni Hardiansyah; Ihsan Mz (Jurnal Bimbingan dan Konseling Terapan, 2022)
The purpose of this study was to determine the acceptability/acceptability of the training design being developed. The research method uses qualitative research and development or development research. This research developed training designs with a behavioral rehearsal with predetermined steps, namely potentials and problems, literature design, design validation, design revision, and product/design testing. The design validation process was carried out by 3 expert validators who are competent in the field of guidance and counseling. The participants in this study were 10 students of IAIN Palangka Raya in terms of having social anxiety with introverted. The findings in this paper show that the acceptability/acceptability of the expert validator obtained an assessment score of 88% with very good criteria with several revisions. Then from the assessment of 10 participants, an assessment score of 90.5% was obtained with very good criteria without revision. The training design developed to reduce social anxiety in students with introverts is feasible and can be used.